Impaired orthostatic blood pressure recovery and cognitive performance at two-year follow up in older adults: The Irish Longitudinal Study on Ageing - Feeney, Joanne (Clin Auton Res, 2016)
BACKGROUND: Prospective investigations of the association between impaired orthostatic blood pressure (BP) regulation and cognitive decline in older adults are limited, and findings to-date have been mixed. The aim of this study was to determine whether impaired recovery of orthostatic BP was associated with change in cognitive function over a 2-year period, in a population based sample of community dwelling older adults. METHODS: Data from the first two waves of the Irish Longitudinal Study on Ageing were analysed. Orthostatic BP was measured during a lying to standing orthostatic stress protocol at wave 1 using beat-to-beat digital plethysmography, and impaired recovery of BP at 40 s post stand was investigated. Cognitive function was assessed at wave 1 and wave 2 (2 years later) using the Mini-Mental State Exam (MMSE), verbal fluency and word recall tasks. RESULTS: After adjustment for measured, potential confounders, and multiple imputation for missing data, the change in the number of errors between waves on the MMSE was 10 % higher [IRR (95 % CI) = 1.10 (0.96, 1.26)] in those with impaired recovery at 40 s. However, this was not statistically significant (p = 0.17). Impaired BP recovery was not associated with change in performance on any of the other cognitive measures. CONCLUSIONS: There was no clear evidence for an association between impaired recovery of orthostatic BP and change in cognition over a 2-year period in this nationally representative cohort of older adults. Longer follow-up and more detailed cognitive testing would be advantageous to further investigate the relationship between orthostatic BP and cognitive decline. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10286-016-0340-3) contains supplementary material, which is available to authorized users.